Determinants of Flow Connectivity in Small-Scale Wetland Irrigation Networks: A Sensitivity Analysis Approach In Aceh Jaya - Ahmad Reza Kasury; Nadri Pratama Putra; Marlina Marlina (Teras Jurnal : Jurnal Teknik Sipil, 2026)
Abstrack   This study aims to analyze the determinants of flow connectivity in small-scale irrigation networks within wetland ecosystems of Aceh Jaya Regency, based on the perceptions of 135 water users. Five primary parameters were evaluated: channel structural stability (X1), channel conveyance condition (X2), sedimentation (X3), flow connectivity (X4), and discharge control performance (X5). Integration of Spearman correlation, ordinal logistic regression, Sobol’ sensitivity analysis, and cluster analysis reveals that canal conveyance condition (X2) performs best. Channel structural stability (X1) shows the lowest performance as a direct impact of wetland characteristics. Unstable soil conditions exacerbate the physical stability of irrigation networks in the region.Correlation findings reveal that cross-sectional stability is significantly and positively related to connectivity (r=0.452), while discharge control performance (X5) shows a negative correlation (r=-0.513). A reverse causality phenomenon is indicated in locations with high water distribution constraints, where control infrastructure tends to be concentrated. Regression analysis confirms that good cross-sectional stability increases the probability of optimal connectivity by up to 2.6 times. Sensitivity analysis results identify flow control as the most critical parameter (STi=0.51), followed by cross-sectional stability (STi=0.44). This research recommends priority interventions in strengthening control infrastructure and cross-sectional stability adaptive to wetland hydrological dynamics based on a farmer cluster approach.   Keywords: Small-scale Irrigation Networks, Flow Connectivity, Wetlands, Sobol’ Sensitivity Analysis   Abstrak   Penelitian ini bertujuan menganalisis determinan konektivitas aliran pada jaringan irigasi skala kecil di lahan basah Kabupaten Aceh Jaya berdasarkan persepsi 135 petani. Lima parameter utama dievaluasi meliputi stabilitas penampang (X1), kebersihan saluran (X2), sedimentasi (X3), konektivitas aliran (X4), dan pengendalian aliran (X5). Melalui integrasi korelasi Spearman, regresi logistik, sensitivitas Sobol’, dan analisis klaster, ditemukan bahwa kebersihan saluran (X2) berkinerja terbaik, sedangkan stabilitas penampang (X1) terlemah akibat kondisi tanah lahan basah yang labil. Hasil korelasi menunjukkan X1 berhubungan positif signifikan dengan X4 (r=0,452), sementara X5 berkorelasi negatif (r=-0,513), mengindikasikan fenomena kausalitas terbalik pada area dengan kendala distribusi air tinggi. Analisis regresi mengonfirmasi bahwa peningkatan kondisi X1 meningkatkan peluang konektivitas aliran (X4) hingga 2,6 kali lipat. Analisis sensitivitas menempatkan pengendalian aliran (X5) sebagai parameter paling kritis (STi=0,51), diikuti X1 (STi=0,44). Penelitian ini merekomendasikan prioritas intervensi pada infrastruktur pengendalian dan stabilisasi penampang yang adaptif terhadap dinamika hidrologi lahan basah berbasis pendekatan klaster petani.   Kata kunci: Jaringan Irigasi Kecil, Konektivitas Aliran, Lahan Basah, Sensitivitas Sobol’